Wdrażanie controllingu w celu poprawy jakości informacji w procesach logistycznych - Chomiak-Orsa, Iwona (Controllership implementation for the purposes of information quality improvement in the logistic processes, 2006)
Nowadays information becomes a significant resource in an enterprise. Its quality is basic element evaluated within Logistics Information System. Logistics Information System management has to improve information quality. So new management concepts are more and more popular. Controllership is one of such management concepts. The main aim of this paper is to present the possibilities of application of controllership tools and techniques to improve information quality, which is needed for obtaining efficient organisation performance.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1136, s. 53-59